2022
DOI: 10.3389/fmed.2022.929709
|View full text |Cite
|
Sign up to set email alerts
|

Inverse association between low-density lipoprotein cholesterol and bone mineral density in young- and middle-aged people: The NHANES 2011–2018

Abstract: ObjectivesLow-density lipoprotein cholesterol (LDL-C) plays an essential part in bone metabolism. However, the correlation between LDL-C levels and bone mineral density (BMD) is still controversial. This study aimed to explore the relationship between LDL-C levels and lumbar BMD in young- and middle-aged people.MethodsWe conducted a cross-sectional study comprising 4,441 participants aged 20–59 from the National Health and Nutrition Examination Survey (NHANES). LDL-C levels and lumbar BMD were used as independ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Furthermore, a study demonstrated an inverse correlation between HDL-C levels and BMD [ 32 ]. In the NHANES 2011–2018 data, a study conducted by Xiao et al found a negative relationship between LDL-C levels and lumbar BMD in the young- and middle-aged population [ 5 ]. Additionally, Wang's study, after accounting for all relevant covariates, revealed an interesting inverted U-shaped curve representing the correlation between HDL-C levels and total BMD among adolescents aged 16–19 [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a study demonstrated an inverse correlation between HDL-C levels and BMD [ 32 ]. In the NHANES 2011–2018 data, a study conducted by Xiao et al found a negative relationship between LDL-C levels and lumbar BMD in the young- and middle-aged population [ 5 ]. Additionally, Wang's study, after accounting for all relevant covariates, revealed an interesting inverted U-shaped curve representing the correlation between HDL-C levels and total BMD among adolescents aged 16–19 [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…As life expectancy has increased, there has been a rise in the prevalence of osteoporosis, leading to a decline in quality of life and an increase in medical expenses. Apart from genetic factors, age, and lifestyle choices [ 3 , 4 ], such as lipid or glucose metabolism [ 5 7 ], have recently drawn considerable attention due to their influence on bone metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Further subgroup analyses after stratification by age indicated negative associations in the age group of 30–49 years. In the subgroup analysis stratified for BMI, there was an inverse correlation between BMD and LDL-C in overweight people (25 ≤ BMI < 30) [ 22 ]. A further NHANES study found a negative association between BMD and LDL-C.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, serum LDL-C and TC levels and the LDL-C/TC ratio of middle-aged and older adults with osteopenia in Southwest China increased signi cantly, and changes in LDL-C and TC in this population were consistent with previous articles. 5,[12][13][14][15][16][17][18] Whether LDL-C/TC is related to the change in bone mass has not been reported in previous articles. For example, in a study of patients with gestational diabetes, it was found that patients with gestational diabetes mellitus with high serum levels of TC and LDL-C have low BMD.…”
Section: Discussionmentioning
confidence: 99%